Biological Activity of Levan Produced from Rhizospheric Soil Bacterium Brachybacterium phenoliresistens KX139300 - Baghdad Science Journal (مجلة بغداد للعلوم, 2018)
Levan is an exopolysaccharide produced by various microorganisms and has a variety of applications. In this research, the aim was to demonstrate the biological activity of levan which produced from B. phenoliresistens KX139300. These were done via study the antioxidant, anti-inflammatory, anticancer and antileishmanial activities in vitro. The antioxidant levan was shown 80.9% activity at 1250 µg/mL concentration. The efficient anti-inflammatory activity of 88% protein inhibition was noticed with levan concentration at 35 µg/mL. The cytotoxic activity of levan at 2500 µg/mL concentration showed a maximum cytotoxic effect on L20B cell line and promastigotes of Leishmani tropica. Levan has dose-dependent anticancer and antileishmanial activities. An addition to the antioxidant, anti-inflammatory and anticancer potential activities of levan, it can be concluded that levan produced from B. phenoliresistens can efficiently be applied as an antileishmanial agent.